Hari Pemungutan Suara dalam Bingkai Media Televisi - Retno Sari Handayani; Syahrizal Syahrizal; Tengku Rika Valentina (LP2M Universitas Sarjanawiyata Tamansiswa, 2021)
The public should be the party that benefits the most in terms of access to information through mass media using public frequencies. Expectations regarding the role of the media are increasingly important during the election period, as in this study it is limited to voting day by choosing TV One and Metro TV as research objects to analyze broadcast content and interpretations made by the media regarding the vote on April 17 2019. This study uses a constructive research approach, with the Robert N. Entman framing analysis methodology presented in a descriptive qualitative manner. The findings in this study indicate that there are educational efforts on live broadcast programs that can be seen in the selection of sources and in the dialogue developed by the two media. Metro TV interpreted that the voting day was running smoothly and that the candidates participated in influencing the peaceful running of the election. Meanwhile, TV One framed the 2019 Election as still running with various problems for voters who had to vote for five different types of elections. The study also found that the media played a role in framing the 2019 elections that were centered on the presidential election, rather than other types of elections. In addition, these two media also provide space for their owners to convey messages to the public who are also figures of national political parties.